Perancangan Sistem informasi Reservasi Restoran Berbasis Web Menggunakan Metode Waterfall (Studi Kasus : Rumah Makan Joglo(RMJ)) - Muhammad Bagas Ramadhan; Nidia Rin Triana; Rishaq Dean Sheva; Saprudin (CV. Multi Kreasi Media, 2025)
Digital transformation in business operations demands more efficient service systems, including in the culinary sector. Rumah Makan Joglo(RMJ) still employs a manual reservation process, leading to issues such as disorganized records, slow service, and the risk of losing potential customers. This study aims to design a web-based restaurant reservation information system using the Waterfall methodology. The development stages included requirement analysis, system design, implementation, and functional testing through black box techniques. The results showed that the system successfully automated table and menu reservations, accelerated payment verification, and improved the accuracy of reservation data management. Functional testing confirmed that all features, from both admin and customer perspectives, performed as expected. This system proves to be an effective solution to enhance service quality and strengthen competitiveness in a digital business environment.